Dislocation-driven SnTe surface defects during chemical vapor deposition growth. (May 2019) - Liu, Pengzi; Xie, Yujun; Miller, Eric; Ebine, Yuta; Kumaravadivel, Piranavan; Sohn, Sungwoo; Cha, Judy J.
Abstract: Topological crystalline insulator (TCI) SnTe has attracted growing interest due to its promise for spintronics and quantum computing applications. Because the topological protection stems from the crystal symmetry for TCIs, crystal defects on the surface of SnTe can strongly influence the topological phases and transport properties. The goal of this work is, therefore, to unveil the origin and evolution of surface defects, such as pits, open cores and steps, observed on SnTe microcrystals and nanostructures synthesized by chemical vapor deposition (CVD). We find that surface pits originate from different types of dislocations in SnTe crystals. Enlarging, deepening, and faceting of surface pits occur by sublimation of open cores and movement of steps during the cooling process of the CVD growth. In contrast, open cores and steps on surfaces form during growth. Surface crystal symmetry, surface polarization and growth conditions contribute to distinct morphologies of the observed surface pits. We show that a fast cooling, instead of the natural cooling, can suppress the formation of surface pits on the SnTe crystals. To decrease the number of open cores and steps on 100 and 111 surfaces of the SnTe microcrystals and nanostructures, the CVD growth conditions need to be further optimized. Graphical abstract: Image 1 Highlights: ● Various surface defects, such as open cores, steps and pits, are common on 100 and 111 surfaces of SnTe micro- and nanocrystals synthesized via chemical vapor deposition (CVD). ● Surface pits originate from dislocations buried under surface planes. ● Enlarging, deepening, and faceting of surface pits are caused by sublimation of open cores and movement of steps. ● Surface pits can be effectively suppressed by fast cooling after the CVD growth.